Influence of the H2O content and the time on the formation of nanostructures in a chemical solution of H2O/HF/NH4F/EG (2018)
The influence of anodizing time on the length, morphology and photoelectrochem-ical properties of TiO2 Nanotubes has been investigated. An optimum anodizing time of 20 min at 20V leads to 220nm long of the nanotubes. By having a detailed control of the electric current one can know exactly the time in which the nanotubes grew and the time in which the process stopped. The FEG-SEM measures show the morphology of the nanotubes and how they come to separate and fall after a certain time. However, the growth of these, is uniform with little remaining material on the surface. For the solution of the anodizing process it is very important to control the amount of water, ethylene glycol and hydrofluoric acid. Small modifications in the solution change the growth time and size of the nanotubes.